Wildlife, fire & future climate : a forest ecosystem analysis - Mackey, Brendan (Brendan G.) (CSIRO Pub., 2002)
The conservation of Earth's forest ecosystems is one of the great environmental challenges facing humanity in the 21st century. All of Earth's ecosystems now face the spectre of the accelerated greenhouse effect and rates of change in climatic regimes that have hitherto been unknown. In addition, multiple use forestry - where forests are managed to provide for both a supply of wood and the conservation of biodiversity - can change the floristic composition and vegetation structure of forests with significant implications for wildlife habitat. Wildlife, fire and future climate: a forest ecosys.